METODE LAFZIYAH DALAM MENGISTINBATKAN HUKUM MENURUT MAZHAB ZAHIRIYAH - Hasnani Siri (DIKTUM: Jurnal Syariah dan Hukum, 2011)
This article discusses the methods Lafziyah in finding the law. Based on assessment results indicated that schools of az-Zahiriyah is a School that in formulating the law sets only adhered to the rules of language (Mafhun al-Lash). This concept is an alternative development of the law formulated solely by this flow, as a consequence of the rejection method of analogy (analogy). In addition to the Quran and al-Sunnah, this school also uses ijma 'friend and al-proof. The concept of al-effective proposition is deemed to appear to give an answer and a chance to anticipate the complexity of problems that may arise in the community.